Application of Problem Based Learning (PBL) Learning Model Environment-Based as an Effort to Improve the Quality of Class V SD Negeri Patemon 02 Semarang - Kurniawati, Septiani Evi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning has not provided a real picture to students. Due to limited methods, teachers need to use other methods. Teacher skills, student activities and learning outcomes have not been maximized. Based on the problem, it is necessary to apply an environment-based Problem Based Learning (PBL) learning model for students. The research uses a CAR research procedure which consists of four steps, namely planning, implementing action, observing, and reflecting. The research design consists of 4 stages in one cycle. The instrument of data collection used the technique of observation, interviews, documentation studies and evaluation sheets. The data analysis technique used qualitative and quantitative analysis. The results of teacher skills have a percentage of success in the first cycle of 76.56% and the second cycle of 89%. The results of student activities have a percentage of 62.5% in the first cycle and 78% in the second cycle. The learning outcomes of students in the first cycle were 70.3% and the second cycle was 85.18%. In conclusion, the environmental-based Problem Based Learning (PBL) model that is applied can improve the quality of learning.